Essential Oil Analysis of Nepeta crispaand N. menthoidesfrom Iran: Essential oil of Nepetagenus - Hasan Hooshdar Tehrani; Bahman Nickavar; Faraz Mojab (Iranian Journal of Pharmaceutical Sciences, 2009)
The composition of the essential oils of Nepeta crispaWilld. and N. menthoides Boiss. and Buhse (Lamiaceae) was investigated by means of gas chromatography(GC) and GC- mass spectrometery (MS). 1, 8-Cineole was the most abundant component in oils: Nepeta crispa(71%) and N. menthoides(41.1%). In the oil of N. crispa, ß-pinene (5%) and δ-terpineol (4.1%) were found to be the major constituents. Dihydromyrcen-1-ol (9.2%), 4-terpineol (7.1%), and geranyl acetate(6.1%) were the predominant compounds in the oil of N. menthoides.